Implementation of Effective Rainfall Forecast Model using Machine Learning - Balamurugan, Kavitha; A., Jose Anand; B., Rammya; R., Dinesh Kumar; K., Kalanithy; N., Mathan J. (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
Rainfall has a significant impact on hydrology and meteorology. To manage resources and make in advance plans to conserve water resources, rainfall prediction is helpful. When predicting rainfall using an existing dataset, machine learning algorithms are equally significant. Data about rainfall is gathered from the KAGGLE website. contains rainfall data that has been collected throughout the past 100 years (1901-2015). Information is recorded and gathered all around India. Using MATLAB software, we developed a system that can forecast rainfall in Tamil Nadu based on this data.